2022
DOI: 10.1093/mnras/stac639
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent modelling of the Milky Way’s nuclear stellar disc

Abstract: The Nuclear Stellar Disc (NSD) is a flattened high-density stellar structure that dominates the gravitational field of the Milky Way at Galactocentric radius 30 ≲ R ≲ 300 pc. We construct axisymmetric self-consistent equilibrium dynamical models of the NSD in which the distribution function is an analytic function of the action variables. We fit the models to the normalised kinematic distributions (line-of-sight velocities + VIRAC2 proper motions) of stars in the NSD survey of Fritz et al., taking the foregrou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 113 publications
(87 reference statements)
14
54
0
Order By: Relevance
“…Both fields are at a distance of about 20 pc from Sgr A* and along the Galactic plane. The volume densities of NSC and NSD at this radius have the same order of magnitude (Sormani et al 2022). Figure 1 shows the regions that our data cover.…”
Section: Observationsmentioning
confidence: 76%
See 2 more Smart Citations
“…Both fields are at a distance of about 20 pc from Sgr A* and along the Galactic plane. The volume densities of NSC and NSD at this radius have the same order of magnitude (Sormani et al 2022). Figure 1 shows the regions that our data cover.…”
Section: Observationsmentioning
confidence: 76%
“…We found that the mean stellar metallicity is decreasing outwards, from the NSC to the NSD, and the transition region lies in between. The volume densities of the NSC and NSD at the transition region have the same order of magnitude, while the density of the NSC at 1 R e is higher by a factor ∼15, and in the very centre by a factor ∼100 compared to the NSD (Sormani et al 2022). The stars in the transition regions are not dominated by one of the two structures, but rather a roughly equal mix of stars belonging to the NSC and NSD.…”
Section: Distinct Formation Histories Of the Nsc And Nsdmentioning
confidence: 82%
See 1 more Smart Citation
“…The largest error (∼ 5%) is observed at 𝑅 ∼ 200 pc, where the potential is actually dominated by the nuclear stellar disc. The latter is not included in the present model and should be added to obtain the total gravitational field at 𝑅 300 pc (Sormani et al 2022). Note also that this circular velocity curve does not include the dark matter component.…”
Section: Resultsmentioning
confidence: 99%
“…Blitz & Spergel 1991;Stanek et al 1994Stanek et al , 1997Babusiaux & Gilmore 2005;Rattenbury et al 2007;McWilliam & Zoccali 2010;Wegg & Gerhard 2013;Simion et al 2017;Sanders et al 2019), and at larger radii, the bar/bulge extends into the long thin bar (Wegg et al 2015). In the very central regions around the suspected ★ E-mail: jason.sanders@ucl.ac.uk (JLS) dynamical centre of the Galaxy, Sgr A*, there is a nuclear stellar cluster (NSC, Schödel et al 2014), and between these two structures sits the nuclear stellar disc (Launhardt et al 2002;Nishiyama et al 2013;Sormani et al 2022). The nuclear stellar disc (NSD) has an extent of ℓ ∼ 1.5 deg and is associated with the central x2 orbits that form in a barred potential.…”
Section: Introductionmentioning
confidence: 99%